1980
DOI: 10.1192/bjp.137.1.17
|View full text |Cite
|
Sign up to set email alerts
|

ECT: II: Patients who Complain

Abstract: Twenty-six subjects who complained of permanent unwanted effects following ECT were compared with two groups of control subjects on a battery of 19 cognitive tests. Many statistically significant differences were found in cognitive functioning, mostly attributable to the level of depression or medication in the complainers. However, after analysis of variance/co-variance some differences still remained, indicating impaired cognitive functioning in the ECT complaining group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(31 citation statements)
references
References 0 publications
0
29
0
2
Order By: Relevance
“…between 9 months and 30 years previously revealed impairment on a range of measures, even after controlling for the effects of illness and medication (Freeman et al, 1980). Despite recommendations that psychiatrists inform patients of non-memory cognitive aftereffects (Calev, 1994) and warn them that 'they are not going to function well on more tasks than they anticipate' (Calev et al, 1995), patients are still routinely not informed about these effects; there is no mention of them in the recommended consent forms of the American Psychiatric Association (APA; 2001), the Royal College of Psychiatrists (2005: Appendix IV) or the manufacturers of ECT equipment.…”
mentioning
confidence: 99%
“…between 9 months and 30 years previously revealed impairment on a range of measures, even after controlling for the effects of illness and medication (Freeman et al, 1980). Despite recommendations that psychiatrists inform patients of non-memory cognitive aftereffects (Calev, 1994) and warn them that 'they are not going to function well on more tasks than they anticipate' (Calev et al, 1995), patients are still routinely not informed about these effects; there is no mention of them in the recommended consent forms of the American Psychiatric Association (APA; 2001), the Royal College of Psychiatrists (2005: Appendix IV) or the manufacturers of ECT equipment.…”
mentioning
confidence: 99%
“…Although the 'Results' section of several papers showed the experience of memory loss amongst a significant proportion of recipients, the 'Discussion' concluded that this did not occur (e.g. Freeman et al, 1980). This discrepancy between the Results and the Discussion did not appear to us scientific -the very accusation often levelled at user-led research.…”
Section: User-centred Systematic Reviewsmentioning
confidence: 83%
“…Psychiatrists may even conclude that permanent memory damage is not a significant problem when their actual results indicate the contrary (Freeman, Weeks, & Kendell, 1980).…”
Section: The Electroconvulsive Therapy (Ect) Reviewmentioning
confidence: 98%